COMPARISON OF VARIOUS EEG ELECTRODE PLACEMENT SYSTEMS TO DETECT EPILEPTIFORM ABNORMALITIES IN INFANTS - Parameswaran, Sajeesh; Anil Kumar, Thankappakurup Vijayamma; Mohan1, Ajith; Thomas, John; Sajeev, Nikhil; Swarnam, Kamala; Pillai, Ananthanarayana Marthanda (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Background: Technical difficulties in placement of whole 10-20 electrode system is not uncommon in neonates and infants. Apart from the full channel many centers uses the modified and amplitude integrated EEG montages to identify seizures.Objective: Efficacy of standard, modified and amplitude integrated EEG electrode placement in infants to detect epileptiform abnormalities.Methods: All routine EEGs from June 2015 to April 2018 were taken. Age â‰¤ 2years at the time of recoding was the inclusion criteria. Digital EEG was performed according to standard 10-20 electrode placement system in all patients. Abnormal EEGs were reanalyzed in different montages like A) 21 electrodes- full channel, B) 10 electrodes- modified long distance and C)4 electrodes- (centro/parietal) respectively. Inter ictal epileptiform discharges (IEDs), seizures, periodic complexes and non-specific dysfunctions were tabulated in all patients. Full channel montages are considered bench mark for the analysisResults: A total 129 EEGs analyzed. A) Full channel standard 21 electrodes montages could identify IEDs in 35, non-specific electrophysiological dysfunction in 9 and burst-suppression pattern in 2 EEGs. B) Modified electrode placement consists of 10 electrodes could identify IEDs only in 26 EEGs and non-specific electro physiological dysfunction in 6 EEGs. A total of 28 nonconvulsive seizures (NCS) recorded in 6 patients; 20 numbers of NCS (71.4%) seen in modified electrode placement (B) and only 16 (57.1%) seen in centro/parietal electrode placement (C)..Conclusion: Standard EEG electrode placement has higher yield in detecting epileptiform abnormalities.